UJI PENGGUNAAN EKSRETA SAPI TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA MACAM VARIETAS SORGUM (Sorghum bicolor L. Moench) - SRI REJEKI AGUSTINAH; PUJI HARSONO; ENDANG SUPRAPTI (JURNAL ILMIAH AGRINECA, 2015)
The study, entitledTestUsingcowexcretaon Growthand ResultsSeveralvarieties ofsorghum(Sorghum bicolorL.Moench) to determine the effecton thegrowth and yield ofsorghumcowexcretafertilizer application. This researchhas beenconductedinHamletNgrombot, PlesanVillage, District Nguter, Sukoharjo, Central JavaByDateMarch 8, 2014untilJune 22, 2014. This study used a factorialmethodwitharchetypalcompleterandomized block design(CRBD) consisting oftwotreatments,a widevarietyconsists of 2levels in varietiesWray(V1) andKeller(V2) and thekinds offertilizercombinationconsisting of4 levelsie an organic fertilizer (E0), solid cattle manure excreta + ½ the recommended dose of an organic fertilizer (E1), liquid cow manure excreta 25% + ½ the recommended dose of an organic fertilizer and half the recommended dose of excreta solid beef (E2), liquid cow manure excreta 10% + ½ the recommended dose of an organic fertilizer and solid excreta half the recommended dose (E3) so that the resulting 8 treatments and their combinations - each repeated 3 times. Data were analyzed by analysis of variance of 5% and 1%, and followed by Duncan test  with a significance level of 5% if there is an interaction between the two treatments. The results of this study indicate that the varieties (V) highly significant in percentage growth parameters, of leaf number and weight of seeds per plot, and no significant difference in the parameters of plant height, stem diameter 30 days after planting and 60 days after planting, panicle length, panicle weight and seed weight per plant.Fertilizercombination treatment(E) differ significantlyintrunk diameterof 30daysafterplanting, significant differencesinplant heightandweight ofseedsper plot, no significant difference inthe percentage ofgrowth, number of leaves, stem diameter 60daysafterplanting, panicle length, panicleweightof plot, plantingseed weight.while the interactionbetweena widevariety andcombination offertilizer(VxE) differ significantlyintrunk diameterandseed weightof plot, no significant difference inthe percentage ofgrowth10daysafterplantingand15daysafterplanting, plant height, leaf number, panicle length, panicleweightof plant, panicleweightof plotandseed weightofplant. The highest yieldis shownbya combination of treatments(V2E2) with900.00gand the lowestvalueindicatedby(V1E2) with avalue of476.67g.